2012
DOI: 10.1007/s11558-012-9150-0
|View full text |Cite
|
Sign up to set email alerts
|

External sources of clean technology: Evidence from the Clean Development Mechanism

Abstract: New technology is fundamental to sustainable development. However, inventors from industrialized countries often refuse technology transfer because they worry about reverse-engineering. When can clean technology transfer succeed? We develop a formal model of the political economy of North-South technology transfer. According to the model, technology transfer is possible if (i) the technology in focus has limited global commercial potential or (ii) the host developing country does not have the capacity to absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…This result is consistent with the social impact hypothesis (Preston & O'Bannon, ), and is in line with several previous empirical studies (Carrillo‐Hermosilla et al, ) because SRFIRM has a positive effect on ECOIN and, as shown above, eco‐innovations affect EXPO. The negative impact of eco‐innovations on exposure to pollution can be explained because the specific knowledge and innovation output of these eco‐innovations are transferred faster to countries and societies and reduce the level of pollution (Bayer & Urpelainen, ). More specifically, the presence of socially responsible firms may help reduce a country's air pollution (Betts, ; Carrión‐Flores & Innes, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is consistent with the social impact hypothesis (Preston & O'Bannon, ), and is in line with several previous empirical studies (Carrillo‐Hermosilla et al, ) because SRFIRM has a positive effect on ECOIN and, as shown above, eco‐innovations affect EXPO. The negative impact of eco‐innovations on exposure to pollution can be explained because the specific knowledge and innovation output of these eco‐innovations are transferred faster to countries and societies and reduce the level of pollution (Bayer & Urpelainen, ). More specifically, the presence of socially responsible firms may help reduce a country's air pollution (Betts, ; Carrión‐Flores & Innes, ).…”
Section: Resultsmentioning
confidence: 99%
“…The negative impact of eco-innovations on exposure to pollution can be explained because the specific knowledge and innovation output of these eco-innovations are transferred faster to countries and societies and reduce the level of pollution (Bayer & Urpelainen, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that CCS is now viewed as one method of reducing greenhouse gases and addressing the problem of global climate change, it may be necessary to transfer CCS technology from countries with high levels of company R&D capacity to those with low levels. However, companies may be reluctant to allow such transfers to take place due to concerns regarding potential loss of competitive advantage in the future (Bayer and Urpelainen 2013). Until these concerns can be resolved successfully, countries will continue relying on technological innovation generated by domestic companies and experiencing constraints on CCS technology development and adoption identified in our research.…”
Section: Discussionmentioning
confidence: 99%
“…If the advantage is small, then institutions for bilateral implementation are optimal. After all, bilateral implementation also has benefits, such as increased technology transfer (Bayer and Urpelainen, 2013) and the possibility of external capacity building. While our model does not emphasize these benefits, their presence is important because otherwise unilateral implementation would dominate bilateral implementation by definition.…”
Section: Unilateral and Bilateral Implementationmentioning
confidence: 99%